Regimental fund accounting a cure to nonprofit organization illness / Sabirin Zayadi - Zayadi, Sabirin (1990)
Accounting language and practices are unacquainted to non-businessman and non-accountant personnel. As such, they do not take an interest in having a second look at figures, statements and report of accounts even if they are related to their own activities. This happens mostly in nonprofit organizations. Most members are oblivious or take for granted the financial position of their association and leave it to the committee members to deal with it and they are satisfied as long as their subscription records are correct.